SISTEM INFORMASI PELAPORAN TRANSAKSI DI BANK BTN SYARIAH BERBASIS JAVA - Kurniyadi, Trisna; Habibie, Muhammad Tri; Pramarta, Pandhu (JTIK (Jurnal Teknik Informatika Kaputama), 2020)
Bank BTN Syariah is one of the Sharia Business Units of Bank Tabungan Negara (Persero) Tbk engaged in sharia-based financial services, in carrying out its banking activities there are still several transaction reporting systems that are still done manually, so the level of employee registration errors is very high and less effective. The purpose of this study is to design a transaction reporting system using the Java-based programming language and this design method uses the Research and Development (R&D) method. The results built on this information system collection of data related to data on receiving and borrowing daily transaction reports making it easier for administrators to manage daily transaction reporting.